SOCIAL SERVICE PROMOTION, COUNSELING AND EDUCATION COVID-19 VACCINATION FOR ADOLESCENTS - Yudianita Kesuma (Fakultas Kedokteran Universitas Sriwijaya, 2021)
The increasing number of incidences and deaths of COVID-19 in Indonesia, especially in South Sumatra which ranks 3rd in Indonesia. For this reason, in addition to efforts to break the chain of transmission of COVID-19 in the form of the Enforcement of Restrictions on Community Activities, which causes all economic, educational, and religious activities to be hampered. For this reason, to reduce the incidence and mortality due to COVID-19, it is in the form of COVID-19 vaccination, in addition to increasing immunity, it also prevents the severity of the disease and reduces mortality due to COVID-19, as well as increasing herd immunity.Vaccination or immunization aims to make a person's immune system recognize and quickly fight bacteria or viruses that cause infection. The goal of the COVID-19 vaccine is to reduce morbidity and mortality due to this virus. Although not 100% able to protect a person from Coronavirus infection, this vaccine can reduce the possibility of severe symptoms and complications due to COVID-19.The Covid-19 vaccination for adolescents began to be carried out in Indonesia based on ten recommendations from IDAI (Indonesian Pediatrician Association) related to Covid-19 vaccination for children aged 12-17 years. For this reason, promotion, counseling, and education are needed to avoid doubts from parents and teenagers who will be vaccinated against COVID-19.